Paradoxical phenomenon in urban renewal practices: promotion of sustainable construction versus buildings’ short lifespan - Shen, Li-yin; Yuan, Hongping; Kong, Xiangfei (International Journal of Strategic Property Management, 2013)
The current urban renewal programs in some developing countries, such as China, are at the expense of demolishing a huge number of existing buildings without distinction. As a consequence, the buildings’ short lifespan due to premature demolition and resultant adverse impacts on environment and society have been criticized for not being in line with sustainable development principles. This study therefore examines impacts of urban renewal practices on buildings’ lifespan by referring to a typical urban renewal region in western China – the Gailanxi region of Chongqing city which is considered representative. Findings show in current practices, little consideration is given to the implications of building demolitions across economic, social and environmental horizons collectively. As a result, premature demolition due to requirements of urban renewal has been a major factor leading to the significantly short lifespan of buildings. This is against the core intention of implementing urban renewal, which is promoting sustainability of the cities. Particularly, buildings’ short lifespan results in consequences against sustainable construction principles, such as energy and resources waste, construction waste generation, environmental pollution, and higher lifecycle costs of buildings. Furthermore, building demolitions without distinction lead to losses of valuable historic buildings. Therefore, the urban renewal process presents a paradoxical phenomenon: the promotion of sustainable construction versus buildings’ short lifespan. The dominance of economic consideration in the decision-making on buildings is considered as the underlying reason to the paradox. The learned experience presented in this study should be built into the decision-making process for carrying out future urban renewal programs.First Publish Online: 19 Dec 2013